EQUINE CHORIONIC GONADOTROPHIN (ECG) STIMULATION DURING THE LUTEAL AND NON-LUTEAL PHASES ON OVARIAN RESPONSE AND EMBRYO QUALITY IN LLAMAS - Evangelista V., Shirley (2009)
The effect of superovulatory treatment during the two phases of the ovarian cycleon follicular growth and embryo quality was evaluated in 45 sexually adult llamas. Animals bearing a >7 mm follicle, observed by ultrasonography, were selected and allocated into 3 groups: T0 (non-stimulated), T1 (superovulatory treatment during the non luteal phase), and T2 (superovulatory treatment during the luteal phase). Animals in groups T1 and T2 received 1 ml of LH (day 0) for synchronization of the follicular wave and 1000 IU of eCG (day 3) as superovulatory treatment. Vaginal sponges impregnated with progesterone were used on days 3 to 7 in T2 to simulate the luteal phase. The induction of the ovulation (day 8) was done through natural mating and the application of GnRH (1 ml). Embryo recovery was done 7 days after natural mating (day 15) on T1 and T2. Similarly, embryo recovery was done 7 days after natural mating and application of GnRH in T0. The number of preovulatory follicles was larger in T1 (11.07 ± 7.53) and T2 (6.13 ± 7.11) than in T0 (1.07 ± 0.26) (p<0.05). The number of corpora lutea was larger in T1 (9.27 ± 3.37) than in T0 (1.07 ± 0.26) and T2 (6.47 ± 4.29) (p<0.05). The number of recovered embryos waslarger in T1 (3.47 ± 4.26) than in T0 (0.33 ± 0.48) and T2 (1.33 ± 2.53). The results showed that superovulatory treatment during the non luteal phase had a better response than superovulatory treatment during the luteal phase.